Radiotherapy Treatment plannINg study Guidelines (RATING): A framework for setting up and reporting on scientific treatment planning studies. (December 2020) - Hansen, Christian Rønn; Crijns, Wouter; Hussein, Mohammad; Rossi, Linda; Gallego, Pedro; Verbakel, Wilko; Unkelbach, Jan; Thwaites, David; Heijmen, Ben
Highlights: Treatment planning studies contribute to novel understanding of radiotherapy. RATING framework helps guide scientists in conducting high-quality research. The guidelines provide in all aspects of planning studies from setting up the study to the reporting. The RATING score sheet calculate a weighted normalised sum score, where the scientists evaluate the study according to a series of questions important to planning studies. The RATING score can help scientists, as well as reviewers and editors, evaluate the quality of the presented research. Abstract: Radiotherapy treatment planning studies contribute significantly  to advances and improvements in radiation treatment of cancer patients. They are a pivotal step to support and facilitate the introduction of novel techniques into clinical practice, or as a first step before clinical trials can be carried out. There have been numerous examples published in the literature that demonstrated the feasibility of such techniques as IMRT, VMAT, IMPT, or that compared different treatment methods (e.g. non-coplanar vs coplanar treatment), or investigated planning approaches (e.g. automated planning). However, for a planning study to generate trustworthy new knowledge and give confidence in applying its findings, then its design, execution and reporting all need to meet high scientific standards. This paper provides a 'quality framework' of recommendations and guidelines that can contribute to the quality of planning studies and resulting publications. Throughout the text, questions are posed and, if applicable to a specific study and if met, they can be answered positively in the provided 'RATING' score sheet. A normalised weighted-sum score can then be calculated from the answers as a quality indicator. The score sheet can also be used to suggest how the quality might be improved, e.g. by focussing on questions with high weight, or by encouraging consideration of aspects given insufficient attention. Whilst the overall aim of this framework and scoring system is to improve the scientific quality of treatment planning studies and papers, it might also be used by reviewers and journal editors to help to evaluate scientific manuscripts reporting planning studies.